Smart Traffic Systems: Dynamic ATraffic in GIS Driving Paths Applications - Halaoui, H.F. (2009 WRI World Congress on Computer Science and Information Engineering : March 31, 2009-April 2, 2009, 2009)
Finding driving directions applications are becoming popular by a variety of users all over the world. Examples of such application can be given: Yahoo maps, MapQuest, and Google Earth as examples of widely used online applications, mobile phone driving direction applications offered by mobile companies, vehicles GPS (global positioning system) and many others. Finding a good driving path between two addresses is subject to many factors where some of them could variables. Examples of these factors are distances, road situation, road traffic, and others. This paper presents the solution of finding a path between two points (addresses) having traffic changing dynamically. It presents spatial databases that are the main databases used in driving direction applications and all GIS applications, discusses currently used solutions and finally proposes a dynamic efficient solution that using the propose dynamic A*Traffic algorithm (an extension of the known artificial intelligent algorithm called A*).